Electronic documents and electronic archives in the USA (Journal of history, 2019)
The current situation in the archival world, the legal basis for the functioning of the archive business, approaches to the theoretical concepts of the science of archives and archival documents, the methodological norms of archival practice, the organization of preservation and the use of documentary heritage, including on the newest media – all these issues represent a serious scientific and practical interest.Archives are a dynamic structure that varies according to the specific conditions of its functioning. At the same time, there are changes not only in functions, structure, storage modes of documents but mainly in the documentary array on traditional and non-traditional media.The article reveals the basic principles that guided the modern archival service of the United States when working with electronic documents and electronic archives. While disclosing the basic principles of this work, attention was focused on studying the experience of applying the latest methodological and technical means in the archives. In the context of this, the article details the problems of managing electronic documents, outlines the activities of NARA to create an electronic government and archive. The introduction of the latest archival technologies and standards when working with electronic documents  and archives, and simplifying access to them, can be used to create models and standards in the field ofarchival science and documentation of Kazakhstan.